ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI SAYURAN DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Synthia Ayu Disha; Dwi Haryono; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze farming income, household income, and welfare level of vegetable farmer households. This research was conducted in Gisting Subdistrict, Tanggamus Regency. This research was conducted in Januari 2017 until Januari 2018 using a survey method. The results showed that croppingpatern A consisted of mustard greens-chili-tomato-bean (planting season I), cabbage (planting season II), whereas, cropping patern B consisted of mustard greens-chili-tomato (planting season I), cabbage (planting season II). Both patterns were advantageous to cultivate (R/C>1). The income of farmer households from on farm activities gives the highest contribution. Household income received by farmers from cropping pattern A was IDR71,410,517.81/year while cropping pattern B was IDR49,781,431.68/year. Based on the criteria of the Central Bureau of Statistics (2014), there were 82.35% of vegetable farmer households in Gisting Subdistrict, Tanggamus Regency which belonged to welfare households.Key words: farmer, income, level of welfare, vegetable